Penggunaan Gadget Dengan Perilaku Prakonsepsi Pada Wanita Usia Subur - faridah, umi; Hidayah, Noor; Wibowo, Irman Ahmad; Elsera, Chori (TRIAGE Jurnal Ilmu Keperawatan, 2024)
Preconception health care is care that refers to biomedical, behavioral, and social preventive interventions that can increase the chances of having a healthy baby. Preconception has an important role in preventing short-term and long-term adverse health impacts for women and their offspring. Reproductive health outcomes will be achieved by focusing on and improving preconception health. it also has the potential to reduce cases of women and babies dying, and many more suffering long-term disabilities, caused by pregnancy and childbirth. Therefore, preconception care is important or necessary to further reduce maternal, newborn, and child mortality. Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are the main indicators of the level of public health. The time approach for collecting data for this research uses survey research with a cross-sectional approach design. There is a relationship between the use of gadgets and preconception behavior at MTs NU Nurul Huda Kudus. The OR value obtained = 6.167 and the P value was 0.05